Presentation of Mathematics Object in Verbal and Symbolic Forms to Increase Conceptual Understanding in Category Statistics Math - Ahmad Yani T; Lucius Chih Huang Chang (JETL (Journal of Education, Teaching and Learning), 2017)
Abstract. This study aims to obtain objective information about the presentation of mathematical objects in the form of verbal and symbolic to improve the conceptual understanding and interest in student learning after being given a lesson with the presentation of mathematical objects in the form of verbal and symbolic in the Mathematical Statistics Course Semester VI Mathematics Education Study Program PMIPA FKIP University of Tanjungpura PontianakThe sample of this research is the fourth semester students who follow the Basic Mathematics course of Mathematics Education program of PMIPA FKIP for the academic year 2016-2017. Data collection is done by giving test result of learning after given treatment. The essay-like test is 10 questions. The result of the research shows that there is an increase of students' learning result through presentation of mathematical object in verbal and symbolic form to improve conceptual understanding in Mathematics Statistics Semester VI Mathematics Education Study Program and there is an increase of learning interest after given learning by presentation of mathematical object in verbal and symbolic form.